2007
DOI: 10.1177/1352458506070704
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients treated with glatiramer acetate: a multicentre, multinational extension of the European/Canadian double-blind, placebo-controlled, MRI-monitored trial

Abstract: Glatiramer acetate (GA) is effective in reducing clinical and magnetic resonance imaging (MRI) activity in relapsing-remitting multiple sclerosis (RRMS). Serial long-term MRI data are lacking for large cohorts of GA-treated patients. The European/Canadian GA study consisted of two consecutive phases, each lasting nine months. The first treatment phase was randomized, double-blind and placebo-controlled. The second was an open-label, active treatment phase with daily administration of 20 mg GA subcutaneously fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
2
48
1
1
Order By: Relevance
“…11 Long-term (mean 5.8 years) follow-up of patients in the European/Canadian study showed that patients who received early treatment with GA were significantly (p = 0.034) less likely to require a walking aid than patients who received GA after a delay of only nine months. 18 Additionally, results of a small proton MR spectroscopy study during the double-blind treatment phase in a subset of patients in PreCISe suggest axonal protection by GA. 19 Despite significant improvements with early versus delayed GA treatment on multiple MRI measures, including brain atrophy, no significant difference between the GA early-and delayed-treatment groups was observed in the rate of confirmed progression of disability, which was reported for only 21% of patients in each group over the five-year study. This may be due in part to the low rate of progression during early MS, but may also reflect the study design, in which patients in the delayed-treatment group received GA immediately upon conversion to CDMS.…”
Section: Discussionmentioning
confidence: 99%
“…11 Long-term (mean 5.8 years) follow-up of patients in the European/Canadian study showed that patients who received early treatment with GA were significantly (p = 0.034) less likely to require a walking aid than patients who received GA after a delay of only nine months. 18 Additionally, results of a small proton MR spectroscopy study during the double-blind treatment phase in a subset of patients in PreCISe suggest axonal protection by GA. 19 Despite significant improvements with early versus delayed GA treatment on multiple MRI measures, including brain atrophy, no significant difference between the GA early-and delayed-treatment groups was observed in the rate of confirmed progression of disability, which was reported for only 21% of patients in each group over the five-year study. This may be due in part to the low rate of progression during early MS, but may also reflect the study design, in which patients in the delayed-treatment group received GA immediately upon conversion to CDMS.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term and real-word data Even with all the limitations of long-term extension studies, due to potential selection bias, available data suggest that the efficacy of GA is maintained over time [63][64][65][66][67][68][69][70][71]. Moreover, there have been no reports of rebound effect or delayed disease reactivation after treatment discontinuation in extensions of clinical trials or postmarketing studies [63,70,72,73].…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
“…Moreover, there have been no reports of rebound effect or delayed disease reactivation after treatment discontinuation in extensions of clinical trials or postmarketing studies [63,70,72,73].…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
See 1 more Smart Citation
“…Продолжен-ное наблюдение за пациентами в открытой фазе данного исследования (94% от изначального числа) установило снижение количества очагов на Т2-взвешенных изобра-жениях в группе с отсроченным началом терапии на 54% и дальнейшее снижение на 24,6% в группе раннего начала терапии [54]. Наблюдение в течение 5 лет за обеими груп-пами не выявило значимых различий в МРТ-картине, од-нако число пациентов без прогрессирования по шкале EDSS было достоверно больше в первой группе [55]. На основании данных долгосрочных наблюдений можно предположить факт установления иммунологической то-лерантности при длительном использовании ГА в группе пациентов, чувствительных к данной терапии.…”
unclassified